Investigating the Banking Digital Transformation Readiness - Babiker, Ammar Elyas; Elfaki, Abdelrahman (Transactions on Engineering and Computing Sciences, 2023)
Banks and financial institutions in Sudan after ban lift are under increasing pressure to digitize services and operations so as to reduce digital gabs with its peer’s institutions worldwide, and be ready for competency in the digital economy. Challenges with disruptive concepts such as IoT, physical systems, cloud computing, big data, artificial intelligence which are called Industry 4.0 with its business counterpart digital transformation face all banks in Sudan. Most banks and institutions are not ready for this digital transformation as they do not have the capabilities or digital literacy needed for digital transformation. In this paper due to the lack in such research work and the specificity of Sudan case which need specific criteria in assessing digital transformation readiness, we have proposed, implemented and testes a novel framework for assessing digital transformation readiness for banks and financial institutes in Sudan. This framework aims to assist banks and financial institutions by providing comprehensive guidance to assess their current situation and how to achieve higher digital transformation in order to maximize the benefits from digital technologies.